Total phenolic content of polygonum minus, centella asiatica, cosmos caudatus and allium sativum - Zakaria, Nooraini (2015)
Polygonum minus, Centella asiatica, Cosmos caudatus and Allium sativum are herbaceous plants which can be found in the region of Malaysia, Vietnam, Thailand and Indonesia. These plants are consumed as ‘ulam’ among Malaysians for health benefits. These herbs are known to have antioxidant properties due to its phenolic content. The purpose of this study is to determine the percentage of extracted yield and total phenolic content (TPC) of individual as well as the mixed extracts (in 1:1 ratio) of P. minus, C. asiatica, C. caudatus and A. sativum. The herbs were extracted by using juice extractor without any solvent. Then, TPC was determined using Folin-Ciocalteu colorimetric method. Results showed that the C. caudatus had the highest yield extraction (24%), C. asiatica (22.5%), A. sativum (12%) and P. minus (8.5%). Among these herbs, P. minus had the highest total phenolic (1388.19 mg TAE/ 100g extract) content followed by A. sativum (1177.87 mg TAE/ 100g extract), C. caudatus (323.59 mg TAE/ 100g extract) and C. asiatica (150.01 mg TAE/ 100g extract). The mixed extracts of P. minus+A. sativum had the highest total phenolic content (1703.59 ± 152.21 mg TAE/ 100g extract) while mixed extracts of C. asiatica+C. Caudatus had the lowest total phenolic content (218.35 ± 18.36 01 mg TAE/ 100g extract). Interestingly some of the mixture showed the synergistic effects compared individual extract alone.